2018
DOI: 10.1186/s13031-018-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis contact-tracing among Syrian refugee populations: lessons from Jordan

Abstract: BackgroundIn response to the influx of displaced Syrians since 2011, the Jordanian National Tuberculosis Program (NTP) implemented a specific Tuberculosis (TB) reduction strategy, including contact-tracing (CT). Contacts of all refugees diagnosed with pulmonary TB (PTB) were registered by the International Organization for Migration and screened for active & latent TB infection (LTBI) in 6 NTP centres.The objectives of this study were to assess prevalence of active TB and LTBI, risk factors for LTBI as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
1
14
1
Order By: Relevance
“…In the current study, as in previous studies, smear positivity of the index case was a strong risk factor for LTBI for all contacts combined [8,10,16]. However, when stratifying by age, this association completely dissipated for contacts below 15 years of age suggesting that children are also at high risk to be infected by smear negative cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, as in previous studies, smear positivity of the index case was a strong risk factor for LTBI for all contacts combined [8,10,16]. However, when stratifying by age, this association completely dissipated for contacts below 15 years of age suggesting that children are also at high risk to be infected by smear negative cases.…”
Section: Discussionsupporting
confidence: 82%
“…Stratified analysis was separately conducted for adults (≥15 years) and children (< 15 years) due to an association of Quan-tiFERON positivity with age [15]. Analysis was further stratified by index case smear results [16]. Significant differences were those with a p ≤ 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Of note, all cases age less than 15 had complete investigations. A recent study in Jordan of contact investigations among Syrian refugee TB cases found a high proportion of contacts were investigated, but noted a need for increased attention to children under 5 [22]. In this evaluation, there were insufficient data on diagnostic tests or treatments provided to investigated contacts to evaluate the effectiveness of the investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of tuberculosis in Jordan is relatively low and estimated to be 5.8 cases per 100,000 inhabitants per year. 23 Tuberculosis was ruled out through negative acid fast bacilli and mycobacterial culture from bronchoalveolar lavage. Negative purified protein derivative testing was utilized in patients who declined bronchopscopy for bronchoalevolar lavage or when the procedure was not feasible at that time or clinically contraindicated.…”
Section: Methodsmentioning
confidence: 99%